Biochar composite with microbes enhanced arsenic biosorption and phytoextraction by Typha latifolia in hybrid vertical subsurface flow constructed wetland. (15th December 2021) - Irshad, Sana; Xie, Zuoming; Kamran, Muhammad; Nawaz, Asad; Faheem,; Mehmood, Sajid; Gulzar, Huma; Saleem, Muhammad Hamzah; Rizwan, Muhammad; Malik, Zaffar; Parveen, Aasma; Ali, Shafaqat
Abstract: Arsenic contamination of ground water is a worldwide issue, causing a number of ailments in humans. As an engineered and integrated solution, a hybrid vertical subsurface flow constructed wetland (VSSF-CW) amended with BCXZM composite ( Bacillus XZM immobilized on rice husk biochar), was found effective for the bioremediation of arsenic contaminated water. Biological filter was prepared by amending top 3 cm of VSSF-CW bed with BCXZM. This filter scavenged ∼64% of total arsenic and removal efficiency of ∼95% was achieved by amended and planted (As + P + B) VSSF-CW, while non-amended (As + P) VSSF-CW showed a removal efficiency of ∼55%. The unplanted and amended (As + B) VSSF-CW showed a removal efficiency of ∼70%. The symbiotic association of Bacillus XZM, confirmed by SEM micrographs, significantly (p ≤ 0.05) reduced reactive oxygen species (ROS) and malondialdehyde (MDA) accumulation in Typha latifolia, hence, increasing the plant growth (2 folds). An increase in the indole acetic acid (IAA) and arsenic accumulation in plant was also observed in As + P + B system. The removal efficiency of the system was compromised after 4th consecutive cycle and 48 h was observed as optimum retention time. The FTIR-spectra showed the involvement of -N-H bond, carboxylic acids, –CH2 stretching of –CH2 and –CH3, carbonyl groups, -C-H, C–O–P and C–O–C, sulphur/thiol and phosphate functional groups in the bio-sorption of arsenic by BCXZM filter. Our study is a first reported on the simultaneous phytoextraction and biosorption of arsenic in a hybrid VSSF-CW. It is proposed that BCXZM can be applied effectively in CWs for the bioremediation of arsenic contaminated water on large scale. Highlights: Hybrid constructed wetland for As removal. BCXZM filter absorbs arsenic in VSSF-CW. Bacillus XZM enhances arsenic pytoextraction in typha. Reduced arsenic sediment pollution after hybrid VSSF-CW operation. Abstract : Enhanced phytoextraction and biosorption of arsenic in hybrid VSSF-CW amended with BCXZM composite and planted with Typha latifolia